Fuel wood efficient dryers and home processing to add value for kokum and uppage fruits in India - Hom, S.; Vasudeva, R.; Hedge, N.; Lamers, H.; Ramanatha, V.; Sthapit, B. (2012)
This flyer gives good insight into the value of uppage fruit (G. gummi-gutta) and kokum (G. indica) and shows how the use of these fruits can contribute to the livelihood and well-being of many rural households. The ‘Conservation and Sustainable Use of Cultivated and Wild Tropical Fruit Diversity: Promoting Sustainable Livelihoods, Food Security and Ecosystem Services’ project identified innovative solutions like driers and value-adding activities as ‘good practices of diversity management’ that can be selected for further strengthening and scaling up within the community and elsewhere.